Profit Optimisation On Risol Products By Using Simplex Method - Palahudin, Palahudin; Dewi, Adinda Maha; Rohayati, Resti; Putri, Salsa Septia; Syehan, Muhammad; Herdiana, Ogin (Jurnal Fokus Manajemen, 2025)
In an era of increasingly fierce business competition, the food industry faces the challenge of meeting consumer demand while managing resources efficiently to maximize profits. This research focuses on optimizing the profitability of risol products, snacks made from flour dough with various fillings, using the simplex method. The research method used is a quantitative approach with descriptive analysis. Data was collected from the Risol XYZ Plant through observations, interviews, and questionnaires. Data analysis is carried out by compiling a mathematical model that describes the function of the goal to maximize the existing advantages and constraints. The results of the analysis show that by using the simplex method, factories can improve production efficiency and profitability. From the calculations carried out, the objective function Z = 75,000X₁ + 50,000X₂, with the constraints of wheat raw materials, breadcrumbs, chicken meat, carrots, potatoes, and production capacity. Strategic recommendations are provided to improve efficiency and integrate sustainability practices in the production process. This research is expected to make a significant contribution to the development of production management and optimization science, as well as practical benefits for the food industry, especially in the production of risol.